IMPLEMENTASI HAK KEKAYAAN INTELEKTUAL (HKI) PADA INDUSTRI BATIK DI PEKALONGAN - Siti Asadah Hijriwati; Esmara Sugeng (LPPM Universitas Pekalongan, 2011)
IPR is a right that arises as a result of human creative action menghsilkan innovative works that can be applied in human life. As an exclusive rights, Protection of Intellectual Property Rights was originally a form of protection provided by the state of the idea or the handiwork of its citizens, and therefore the rights to the Intellectual Property is fundamentally territorial statehood. Recognition of Intellectual Property Rights protection in a country does not mean the protection of Intellectual Property Rights in other countries. Implementation provisions concerning Intellectual Property Rights have been implemented but have not been up this is due because of the perception of a diverse society on the one side are many who regard IPR has not been necessary because it would limit a person to do good to fellow humans, but there are also people who have started realizing the importance of IPRs thus sought to protect the IPR in this regard is Copyright and Trademark Rights. But in the implementation of the IPR there are also constraints that accompany the marketing system that has not been good, often change-change that motif as well as limited capital and human resources.Key words: Intellectual Property Rights, implementation and public perception.